Effect of raw material microbial contamination over microbiological profile of ground and pelleted feeds - Prió P.; Gasol R.; Soriano R.C.; Pérez-Rigau A. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
In order to evaluate the effect of Salmonella and Clostridium contamination in raw materials and its influence on Salmonella and Clostridium contamination in feedstuffs, results of 1300 analyses are processed. The percentage level of Salmonella contamination in raw materials has a clear influence on Salmonella contamination in non-pelleted feedstuffs (P less than 0.05); however, considering pelleted feedstuffs, the relationship was not significant. The Salmonella contamination in pelleted feedstuffs is due to recontamination in the cooler, the truck or the silo and is independent of the percentage of contamination of raw materials. On the other hand, considering Clostridium perfringens, no significant relationships were found among the contamination percentage of raw materials and feedstuffs (meal and pelleted). Results are according to the well-known capacity of C. perfringens to resist high temperatures and form spores.
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)